1971
DOI: 10.1073/pnas.68.9.2131
|View full text |Cite
|
Sign up to set email alerts
|

Regulation by Calcium of In Vivo Synthesis of 1,25-Dihydroxycholecalciferol and 21,25-Dihydroxycholecalciferol

Abstract: A metabolite of vitamin D believed to be the metabolically active form in the intestine has recently been isolated in pure form from intestine and unequivocally identified in this laboratory as 1,25-dihydroxycholecalciferol (1,25-(OH)2D3)(1, 2). Simultaneously, Lawson et al. provided evidence for this structure with a partially purified material from kidney homogenates (3). This metabolite acts more rapidly than 25-(OH)D3 to initiate intestinal calcium transport (4-6). The kidney is the site of synthesis of 1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
113
1
2

Year Published

1973
1973
2008
2008

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 426 publications
(119 citation statements)
references
References 19 publications
3
113
1
2
Order By: Relevance
“…Also, increased calcium ions can inhibit this transformation by the direct action on the parathyroid and calcitonin secretion rates (BOYLE et al, 1971). In the present study the observed decrease in the plasma calcium levels on day 15 and day 30 may be explained on the basis that the elevated blood calcium has suppressed the secretion of parathyroid hormone, thus affecting the formation of 1,25(OH) 2 D 3 .…”
Section: Discussionmentioning
confidence: 52%
“…Also, increased calcium ions can inhibit this transformation by the direct action on the parathyroid and calcitonin secretion rates (BOYLE et al, 1971). In the present study the observed decrease in the plasma calcium levels on day 15 and day 30 may be explained on the basis that the elevated blood calcium has suppressed the secretion of parathyroid hormone, thus affecting the formation of 1,25(OH) 2 D 3 .…”
Section: Discussionmentioning
confidence: 52%
“…Intestinal mechanisms which influence adaptation to a calcium-deficient diet are stimulation of calcium binding protein formation (37), increase in Ca++ ATPase activity (28), and the increased formation of active vitamin D metabolites (24). The latter mechanism is influenced by calcium content of the renal cell: decreased calcium leads to increased 1,25-dihydroxycholecalciferol formation, whereas increased calcium increases the formation of the relatively inactive 24,25-dihydroxy derivative of vitamin D (5). N o information is available about the age at induction of these mechanisms or whether they are present at birth in the human.…”
Section: Discussionmentioning
confidence: 99%
“…Crowell et al ( 5 ) showed that dogs lose their purines irreversibly during hemorrhagic shock. Saugstad (12) showed that the oxypurine level in umbilical cord plasma is increased in newborn infants with clinical signs of intrauterine hypoxia.…”
Section: Theorymentioning
confidence: 99%
“…An endotracheal tube was passed anfd the dogs were ventilated with a Harvard respirator. Inulin, p-aminohippurate (PAH) and aqueous vasopressin (ADH) were infused in physiological saline solution at a rate of 1 ml/min in quantities sufficient to provide plasma levels of [20][21][22][23][24][25][26][27][28][29][30] mg/100 ml and 1-3 mg/100 ml for the former two substances, and to deliver 30-60 mU/kg per h of the latter. After an equilibration period of 50-60 min, the following experimental maneuvers were performed.…”
Section: Methodsmentioning
confidence: 99%